Analisa Rekomendasi Buku Bacaan Berdasarkan Histori Peminjaman di Perpustakaan Universitas Katolik Santo Thomas Medan Menggunakan Metode Algoritma Apriori - Nainggolan, Huminsa Roganda; Purba, Doni El Rezen (KAKIFIKOM : Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer, 2024)
As time goes by, the amount and scope of data used by society is increasing. Therefore, an effective method is needed to manage this data into information that can be reused. Data mining is a data processing technique used to identify new knowledge. Data processing can help humans in managing the collection and utilization of accumulated data. This research aims to explore association rules in reading book recommendations using the Apriori algorithm method. The implementation of the Apriori algorithm will apply association rules to find linkage patterns in book borrowing data at the Santo Thomas Catholic University Medan Library. By applying the Apriori Algorithm method to borrowing books in libraries, it is hoped that linkage patterns can be revealed which can serve as a guide for librarians in determining the required book preparation. This research specifically focuses on book borrowing data at the Santo Thomas Catholic University Medan library, with the hope of providing insight into visitors' reading needs and interests. It is hoped that the results of implementing the Apriori Algorithm can provide valuable information for librarians to make more focused decisio in determining the book collection to be prepared.